État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

Enjeux de santé des aînés francophones vivant en situation minoritaire : une analyse différenciée selon les sexes - van Kemenade, Solange; Bouchard, Louise; Bergeron, Christian (Reflets, 2015)
La recherche en santé sur les Communautés de langue officielle vivant en situation minoritaire révèle des disparités. Le fait d’être minoritaire dans une société, conjointement avec d’autres déterminants, comme le statut socioéconomique, l’éducation en santé, et le fait de ne pas avoir un soutien social contribuent aux disparités de santé. Dans le contexte du vieillissement plus marqué des populations de langue officielle vivant en situation minoritaire, nous avons examiné la situation des aînés francophones. Pour cela, une analyse secondaire des données issues de l’Enquête sur la santé des collectivités canadiennes (ESCC) a été réalisée. Nous présentons dans cet article, une analyse différenciée de leur situation sociosanitaire selon le sexe et le genre en dressant le portrait des états de santé, des incapacités et des besoins sur le plan des soins de santé. Mots-clés : aînés francophones, situation minoritaire, santé, accès aux soins, services de santé, sexe, langues officielles, Canada, Enquête de santé dans les collectivités canadiennes

La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)

Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire - Bouchard, Louise; van Kemenade, Solange (La santé communautaire en 4 actes : repères, acteurs, démarches et défis, 2016)

Précarité des populations francophones âgées vivant en situation linguistique minoritaire - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Sedigh, Golnaz; Silva, Erika. E.; Sucha, Ewa (Minorités linguistiques et société, 2015)
Le vieillissement des populations s’est considérablement accentué ces dernières décennies et ce plus particulièrement pour la population francophone vivant en situation linguistique minoritaire au Canada. Nos analyses secondaires de l’Enquête sur la santé des collectivités canadiennes (ESCC) révèlent qu’une grande proportion d’aînés francophones n’a pas de diplôme d’études secondaires et se situe dans le quintile de revenu le plus faible. Des analyses multidimensionnelles des données montrent que les déterminants de la pauvreté tels que le revenu et l’éducation exercent une influence sur la pauvreté des personnes âgées, mais que la langue et l’appartenance à la minorité francophone y contribuent de façon spécifique, ce qui constitue une donnée nouvelle. Mots-clés : vieillissement, minorités linguistiques, personnes âgées, pauvreté, déterminants sociaux de santé

Language as an important determinant of poverty in the aging Francophone minority population in Canada - Bouchard, Louise; Sedigh, Golnaz; Batal, Malek; Imbeault, Pascal; Makvandi, Ewa; Sylva de la Vega, E. (The International Journal of Aging and Society, 2013)
Six cycles of the Canadian Community Health surveys (CCHS) from 2001 to 2009 were used to compare the income and health of the minority French-speaking aging population (over 65 years of age) to the majority English-speaking group in Canada, excluding Quebec. A sequential multivariate logistic regression analysis showed that men and women of the minority French-speaking population of this age group, living in Canada outside the province of Quebec, are more likely to be in the poorest income quintile than their English-speaking counterparts. This disparity remains significant even after controlling for residence (province and urban/rural), household makeup (living alone or not), immigration status, education, employment, health status, chronic diseases, and restrictions in activities. Independently of other key socio-demographic factors modulating health, our results also show that being in the poorest income quintile is associated with a poor self-perceived health, a finding that was more prevalent in the French-speaking aging population living in situation of minority.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.